Cuprotosis-related signature predicts overall survival in clear cell renal cell carcinoma - Zhang, Fan; Lin, Junyu; Feng, Dechao; Liang, Jiayu; Lu, Yiping; Liu, Zhihong; Wang, Xianding (Frontiers in Cell and Developmental Biology, 2022)
Background: Cuprotosis is a new form of programmed cell death induced by copper. We first explore the correlation of cuprotosis with clear cell renal cell carcinoma (ccRCC) and developed a cuprotosis-related signature to predict the prognosis of patients with ccRCC. Methods: The clinical and transcriptomic data of ccRCC patients were downloaded from The Cancer Genome Atlas and cBioPortal datasets, and cuprotosis-related gene sets were contained from previous study. A cuprotosis-related signature was developed and verified. Immune cell infiltrates and the corresponding signature risk scores were investigated. Two independent cohorts of clinical trials were analyzed to explore correlation of the signature risk score with immune therapy response. Results: A signature containing six cuprotosis-related genes was identified and can accurately predict the prognosis of ccRCC patients. Patients with downregulated copper-induced programmed death had a worse overall survival (hazard ratio: 1.90, 95% CI: 1.39-2.59, P<0.001). Higher signature risk score was significantly associated with male (P=0.026), higher tumor stage (P<0.001), and higher histological grade (P<0.001). Furthermore, signature risk score was positively correlated with the infiltration of B cell, CD8+ T cell, NK cell, Treg, and T cells, whereas negatively correlated with eosinophils, mast cell, and neutrophil. However, no correlation between cuprotosis and response to anti-PD-1 therapy was found. Conclusion: We established a cuprotosis signature which can predict the prognosis of patients with ccRCC. Cuprotosis was significantly correlated with immune cell infiltrates in ccRCC.